Learn more about

Refine search

Results (displaying matches 1-50 of 11575) Next

Label Class Equation Sato-Tate \(\overline{\Q}\)-simple \(\GL_2\) Rank*
448.a.448.1 448.a \(y^2 + (x^3 + x)y = x^4 - 7\) $N(G_{1,3})$ 0
504.a.27216.1 504.a \(y^2 + (x^3 + x)y = 3x^4 + 15x^2 + 21\) $G_{3,3}$ 0
523.a.523.2 523.a \(y^2 + xy = x^5 - 31x^4 - 110x^3 + 21x^2 - x\) $\mathrm{USp}(4)$ 0
640.a.81920.1 640.a \(y^2 + x^3y = 3x^4 + 13x^2 + 20\) $N(G_{1,3})$ 0
644.a.659456.1 644.a \(y^2 + (x^2 + x)y = -3x^6 - 13x^5 + 4x^4 + 51x^3 + 4x^2 - 13x - 3\) $G_{3,3}$ 0
686.a.686.1 686.a \(y^2 + (x^2 + x)y = x^5 + x^4 + 2x^3 + x^2 + x\) $N(G_{1,3})$ 0
720.a.6480.1 720.a \(y^2 + (x^3 + x)y = 2x^4 + 7x^2 + 5\) $G_{3,3}$ 0
784.a.43904.1 784.a \(y^2 + (x^3 + x)y = 4x^4 + 27x^2 + 56\) $G_{3,3}$ 0
841.a.841.1 841.a \(y^2 + (x^3 + x^2 + x)y = x^4 + x^3 + 3x^2 + x + 2\) $G_{3,3}$ 0
862.a.862.1 862.a \(y^2 + (x^3 + 1)y = x^5 - 2x^4 - 7x^3 + 7x^2 + 2x + 5\) $\mathrm{USp}(4)$ 0
882.a.302526.1 882.a \(y^2 + (x^3 + 1)y = x^5 - 2x^4 - 5x^3 + 11x^2 - 12x + 5\) $G_{3,3}$ 0
930.a.930.1 930.a \(y^2 + (x^2 + x)y = -x^5 - 7x^4 + 37x^2 - 45x + 15\) $G_{3,3}$ 0
960.a.245760.1 960.a \(y^2 = 2x^5 + x^4 + 4x^3 + x^2 + 2x\) $G_{3,3}$ 0
960.a.368640.1 960.a \(y^2 = x^5 + 13x^4 + 44x^3 + 13x^2 + x\) $G_{3,3}$ 0
960.a.983040.1 960.a \(y^2 = x^5 - 2x^4 - x^3 - 2x^2 + x\) $G_{3,3}$ 0
961.a.961.3 961.a \(y^2 + (x^3 + x + 1)y = x^5 + x^4 + x^3 - x - 1\) $G_{3,3}$ 0
961.a.923521.1 961.a \(y^2 + (x^3 + x^2 + 1)y = -5x^4 + 4x^3 + 3x^2 - 2x - 3\) $G_{3,3}$ 0
990.a.8910.1 990.a \(y^2 + (x^2 + x)y = 3x^5 + 4x^4 + 7x^3 + 4x^2 + 3x\) $G_{3,3}$ 0
990.a.240570.1 990.a \(y^2 + (x^2 + x)y = 3x^5 + 28x^4 + 72x^3 + 28x^2 + 3x\) $G_{3,3}$ 0
1038.a.1038.2 1038.a \(y^2 + (x^3 + 1)y = x^4 + 2x^2 + x + 1\) $\mathrm{USp}(4)$ 0
1088.a.1088.1 1088.a \(y^2 + (x^3 + x^2 + x + 1)y = x^4 + x^3 + 2x^2 + x + 1\) $N(G_{3,3})$ 0
1088.b.2176.1 1088.b \(y^2 + (x^3 + x)y = 4x^4 + 24x^2 + 34\) $N(G_{1,3})$ 0
1088.b.2176.2 1088.b \(y^2 + (x^3 + x)y = -5x^4 + 24x^2 - 34\) $N(G_{1,3})$ 0
1122.a.1122.1 1122.a \(y^2 + (x^2 + x)y = x^5 + 7x^4 - 43x^2 + 51x - 17\) $G_{3,3}$ 0
1146.a.2292.1 1146.a \(y^2 + xy = x^5 + 3x^4 + 5x^3 + 4x^2 + 2x\) $\mathrm{USp}(4)$ 0
1176.a.2352.1 1176.a \(y^2 + (x^3 + x)y = x^4 + 3x^2 + 3\) $G_{3,3}$ 0
1184.a.606208.2 1184.a \(y^2 = x^6 - 2x^5 + 5x^4 - 4x^3 + 6x^2 - 2x + 2\) $\mathrm{USp}(4)$ 0
1200.a.450000.1 1200.a \(y^2 + (x^3 + x)y = 4x^4 + 25x^2 + 45\) $G_{3,3}$ 0
1210.a.1210.1 1210.a \(y^2 + (x^3 + x)y = 3x^3 - 2x^2 + 6x + 2\) $G_{3,3}$ 0
1270.a.1270.1 1270.a \(y^2 + (x^3 + 1)y = -2x^4 + 5x^2 - 2x - 3\) $\mathrm{USp}(4)$ 0
1320.a.2640.1 1320.a \(y^2 + (x^3 + x)y = -x^6 + 9x^4 - 40x^2 + 55\) $G_{3,3}$ 0
1328.a.1328.1 1328.a \(y^2 + x^2y = x^5 - 3x^4 - 9x^3 - 5x^2 - 4x - 5\) $\mathrm{USp}(4)$ 0
1344.a.4032.2 1344.a \(y^2 + xy = -x^6 + 12x^4 - 48x^2 + 63\) $N(G_{1,3})$ 0
1344.b.172032.1 1344.b \(y^2 = x^5 - 11x^4 + 32x^3 - 11x^2 + x\) $G_{3,3}$ 0
1386.a.9702.1 1386.a \(y^2 + (x^2 + x)y = x^5 + 20x^4 + 104x^3 + 20x^2 + x\) $G_{3,3}$ 0
1440.a.116640.1 1440.a \(y^2 + (x^3 + x)y = 5x^4 + 39x^2 + 90\) $G_{3,3}$ 0
1444.b.109744.1 1444.b \(y^2 + x^3y = -4x^4 + 16x^2 - 19\) $G_{3,3}$ 0
1536.b.49152.2 1536.b \(y^2 + x^3y = 3x^4 + 11x^2 + 12\) $N(G_{1,3})$ 0
1536.c.98304.1 1536.c \(y^2 + y = 4x^6 - 12x^5 + 3x^4 + 14x^3 - 5x^2 - 4x + 1\) $N(G_{1,3})$ 0
1568.a.1568.1 1568.a \(y^2 + (x^3 + x)y = x^4 + 3x^2 + 2\) $G_{3,3}$ 0
1568.a.43904.1 1568.a \(y^2 + (x^3 + x)y = -5x^4 + 27x^2 - 56\) $G_{3,3}$ 0
1600.a.409600.1 1600.a \(y^2 = x^6 - 2x^2 - 1\) $G_{3,3}$ 0
1649.a.159953.1 1649.a \(y^2 + (x^3 + x^2 + x)y = x^4 + 3x^3 + 4x^2 + 6x + 5\) $\mathrm{USp}(4)$ 0
1650.a.371250.1 1650.a \(y^2 + (x^2 + x)y = x^5 - 11x^4 + 30x^3 - 11x^2 + x\) $G_{3,3}$ 0
1656.a.804816.1 1656.a \(y^2 + xy = 2x^5 - 6x^4 + 13x^3 - 13x^2 + 9x\) $\mathrm{USp}(4)$ 0
1665.a.1665.1 1665.a \(y^2 + (x^3 + x^2 + 1)y = x^4 + x^3 + 2x^2 + 2x + 1\) $\mathrm{USp}(4)$ 0
1680.b.215040.1 1680.b \(y^2 + xy = 4x^5 + 25x^4 + 44x^3 + 15x^2 + x\) $\mathrm{USp}(4)$ 0
1680.c.241920.1 1680.c \(y^2 + (x^2 + 1)y = 135x^6 - 96x^4 + 22x^2 - 2\) $G_{3,3}$ 0
1696.a.217088.1 1696.a \(y^2 + (x^2 + 1)y = x^5 - 24x^4 - 28x^3 - 22x^2 - 7x - 1\) $\mathrm{USp}(4)$ 0
1696.b.434176.1 1696.b \(y^2 + xy = x^6 - 2x^5 + 2x^4 + 9x^3 - 12x^2 + 3x + 26\) $N(G_{3,3})$ 0
Next

Download all search results for